Antitumor activity of polyelectrolytes-metal complexes - Karahan, Mesut; Ozturkcan, S. Arda; Mustafaeva, Zeynep (ARS DOCENDI, 2013)
The interactions between anionic polyelectrolytes [polyacrylic acid, poly(methyl vinyl ether-co-maleic anhydrate)] and copper ions in aqueous solution (pH 7.0) were investigated by dynamic light scattering, UV-visible and fourier transform infrared spectroscopic techniques. Viscosity was also measured by ubbelohde automatic viscometer. Observations indicate that the ratio of ingredients, the nature of the metal ions and their environmental conditions affect the formation of soluble and insoluble Polyelectrolyte-Metal complexes. These binary complexes were tested in vitro as potential antitumor agents with Human Embryonic Kidney 293 cells. Depending on the ratio and sequence of mixing of components in the formation of Polyelectrolyte-Copper complexes, it was observed that the most stable water soluble polycomplexes prepared exhibited a high antitumor activity in the ratio of n(Cu)(2+)/n(AA): 0.4 and n(Cu)(2+)/n(MVE-MA): 0.5, respectively.
Keywords: Biopolymer; copper ions; polyelectrolyte-metal complex; antitumor activity; SCHIFF-BASE LIGANDS; DNA-BINDING; CHITOSAN; COPPER; Biotechnology & Applied Microbiology